2020
DOI: 10.1021/acsabm.0c01087
|View full text |Cite
|
Sign up to set email alerts
|

Facile Nanoimprinting of Robust High-Aspect-Ratio Nanostructures for Human Cell Biomechanics

Abstract: High-aspect-ratio and hierarchically nanostructured surfaces are common in nature. Synthetic variants are of interest for their specific chemical, mechanic, electric, photonic, or biologic properties but are cumbersome in fabrication or suffer from structural collapse. Here, we replicated and directly biofunctionalized robust, large-area, and high-aspect-ratio nanostructures by nanoimprint lithography of an off-stoichiometric thiol–ene-epoxy polymer. We structuredin a single-step processdense arrays of pilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…NIL enables high-resolution and cost-effective manufacturing of micropatterned and nanopatterned surfaces and has found great potential for applications in life sciences. For instance, we recently developed a method for facile nanoimprinting of high-aspect-ratio nanotopographies, which modulate the mechanosensing of human hepatic cells and provide precise spatial control of cell attachment (Zandi Shafagh et al, 2020). NIL has also been implemented for the fabrication of microfluidic and nanofluidic devices with nanochannels (Sun et al, 2016).…”
Section: B Fabrication Techniquesmentioning
confidence: 99%
“…NIL enables high-resolution and cost-effective manufacturing of micropatterned and nanopatterned surfaces and has found great potential for applications in life sciences. For instance, we recently developed a method for facile nanoimprinting of high-aspect-ratio nanotopographies, which modulate the mechanosensing of human hepatic cells and provide precise spatial control of cell attachment (Zandi Shafagh et al, 2020). NIL has also been implemented for the fabrication of microfluidic and nanofluidic devices with nanochannels (Sun et al, 2016).…”
Section: B Fabrication Techniquesmentioning
confidence: 99%
“…The OSTE+ polymers demonstrated a broad range of surface functional adaptability and the ability to form direct bonds with substrates, which made them versatile for various microfluid-based device applications. , Simultaneously, the dual-cure polymerization process of these polymers was also exploited with tailored mechanical properties for various flexible surfaces as well as optical property modification. Further, by varying the process parameters such as the thiol weight percentage, UV polymerization dose, thermal curing time, and initiator concentration, ,, various surface densities of the thiol group on the patterned OSTE+ thin film can be obtained. Subsequently, these polymers have been exploited as photonic platforms by integrating microchannel-based , Mach–Zehnder interferometric devices by room-temperature-assisted direct and adhesive-free bonding techniques. Further, Zhou et al showed that the thiol–ene polymer-based microarrays could be used as biostickers, could be one-step biofunctionalized, and possess a biocompatible covalent surface to monitor protein and DNA interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Carlborg et al 45 have studied the dual-cure polymerization process of the thiol-ene and OSTE + polymer to develop tunable surface properties for different smart applications such as biocompatible microfluidic devices 45,46 and microarray surfaces 43,45 for DNA hybridization and cell sorting. Further, this OSTE + polymer has been utilized to fabricate on-chip photonic devices by integrating microchannels 45,47 and Mach-Zehnder 10 optical interferometric structures that perform in the visible spectral region. In addition, several studies have been focused on tuning the surface functional properties of OSTE +based micro/nanostructured polymeric devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have been focused on tuning the surface functional properties of OSTE +based micro/nanostructured polymeric devices. 42,44,47 Recently, the electro-optical response has also been studied in the polymeric device using cavity resonators which was fabricated from OSTE + and P3-HT sandwich materials. 48 These polymeric materials are evolving as smart conducting polymers that could lead prospective innovations in the area of optoelectronic for low-cost multitasking sensor development.…”
Section: Introductionmentioning
confidence: 99%